Strategies for Women as Key Actors in Resolving Conflicts Over Communal Forests in Pubabu-Besipae - M. Angela Merici Siba; Ronaldus Nurak; Fridus Bria; Yosef Kristoforus Taekab (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study found that there's a conflict over customary forests between the Pubabu-Besipae community and the East Nusa Tenggara provincial government. This conflict started when the forest was made into a pilot area for livestock intensification, then the forestry department turned it into a state forest. As a result, the forest was cleared for the government's interests, and the community didn't know about it. The community naturally rejected this because they felt that under the cooperation agreement, the forest was only designated as a pilot area for livestock intensification. There was no agreement regarding the clearing of the forest or the extension of permits to use the forest. This is what led to the conflict and the struggle over the forest by the community. Using qualitative research methods, the researcher will explain the phenomenon of the Pubabu-Besipae forest conflict, with the subjects being Pubabu women, the women's community Solidaritas Perempuan, and Komnas Perempuan. Data collection techniques include document studies, which involve collecting data from various sources such as journals, newspapers, and articles. The analysis technique uses descriptive analysis, which involves analyzing and explaining the findings. The research results show that the strategies implemented by women actors have influenced the resolution of the Pubabu-Besipae forest dispute. The strategies implemented include negotiations, protests, sending recommendation letters, and filing complaints with institutions.